Comparison Of Buerger Allen Exercise With 3 Physical Therapy Modalities On The Value Of Ankle Brachial Index In Patients With Type Ii Diabetes Mellitus - Ikhsan Ibrahim; Nur Aisyah; Suaib Suaib; Ikhsan Ibrahim (International Journal of Health and Pharmaceutical (IJHP), 2024)
Hyperglycemia is one of the problems of people with Diabetes Mellitus, poorly controlled hyperglycemia conditions can cause complications, one of which is impaired peripheral vascular flow which can cause diabetic wounds. Vascularization disorders can be prevented by Buerger Allen Exercise therapy and 3 Physical Therapy Modalities to increase Ankle Brachial Index (ABI) values. The purpose of this study was to compare the effect of Buerger Allen Exercise and 3 Physical Therapy Modalities on ABI values in people with type II Diabetes Mellitus. The design of this study was Quasi Experiment Pre and post test two groups with 15 respondents of group A given Buerger Allen Exercise intervention and 15 respondents of group B given 3 Physical Therapy Modalities intervention. The results showed that there was an increase in ABI values after intervention in both groups with the difference in the Buerger Allen Exercise group increase of 0.050 while the Modaliatas Physical Therapy group amounted to 0.113. In conclusion, there was an increase in ABI values in both groups after the intervention but group 3 Modaliatas Physical Therapy had a higher increase. Intervention 3 Modaliatas Physical Therapy can be recommended as one of the alternative therapies as a prevention of complications of peripheral arterial disease.